Computer Networks / Second Edition - Tanenbaum, Andrew S. (Prentice Hall International, 1989)
Introduction, The Physical Layer, The Medium Access Sublayer, The Data Link Layer, The Network Layer, The Transport Layer, The Session Layer, The Presentation Layer, The Application Layer, Reading List and Bibliography, Index.